Cutibacterium acnes lysate improves cellular response against Candida albicans, Escherichia coli and Gardnerella vaginalis in an in vitro model of vaginal infection - Francesco Ricchi; Samyr Kenno; Natalia Pedretti; Giulia Brenna; Francesco De Seta; Francesco De Seta; Andrea Ardizzoni; Eva Pericolini (Frontiers in Cellular and Infection Microbiology)
IntroductionThe vagina is a finely balanced microecological environment. The rupture of this balance leads to dysbiosis, which causes the resident microbiota to be overcome by pathogens. This event triggers the onset of gynecological infectious diseases, normally treated with antimicrobial drugs, considered to date as the gold standard; yet the increasing rate of drug resistance requires novel approaches and alternative therapeutic strategies. Bacterial lysates, obtained by mechanical or chemical crushing of the bacterial cell walls, contain several antigens and Pathogen-Associated-Molecular-Patterns (PAMP) molecules that through the priming of epithelial and innate immune cells could improve the responses to the pathogens.Materials and methodsWe evaluated the effect of a bacterial lysate (BL) obtained by Cutibacterium acnes on the response of a human vaginal epithelial cell line and a murine macrophage cell line to the infection by C. albicans, E. coli and G. vaginalis. By priming the cells with BL, the mitochondrial Reactive Oxygen Species (mtROS) production, the cellular damage, the impairment of microbial growth, the phagocytic and killing capacity and the secretion of cytokines and chemokines were assessed.ResultsBL did not show any direct antimicrobial effect nor any toxicity for the cell lines employed. Upon infection with C. albicans, the BL-primed cells were shown to increase the production of mtROS, to be more resistant to pathogen-mediated cell damage, and to reduce the microbial growth. BL-primed macrophages displayed also an increased phagocytic and killing activity against C. albicans, E. coli and G. vaginalis. Cytokines and chemokines secretion by BL-primed vaginal epithelial cells was also modulated upon infection with C. albicans, E. coli and G. vaginalis.DiscussionOverall, the results shown here point to the possible role of BL in priming epithelial and phagocytic cells and to improve their response against bacterial and fungal pathogens. These data indicate that the use of this (and, in future, other bacterial lysates) may provide a promising novel approach to handle lower genital tract infections through the reinforcement of local immunity.